2002
DOI: 10.1203/01.pdr.0000028057.79132.1f
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine Suppresses Nitric Oxide Production and Attenuates Hypoxic-Ischemic Brain Injury in Neonatal Rats

Abstract: Nitric oxide and excitatory amino acids contribute to hypoxic-ischemic brain injury. Agmatine, an endogenous neurotransmitter or neuromodulator, is an inhibitor of nitric oxide synthase and an antagonist of N-methyl-D-aspartate receptors. Does agmatine reduce brain injury in the rat pup hypoxicischemic model? Seven-day old rat pups had right carotid arteries ligated followed by 2.5 h of hypoxia (8% oxygen). Agmatine or vehicle was administered by i.p. injection at 5 min after reoxygenation and once daily there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 21 publications
1
30
1
1
Order By: Relevance
“…Exogenous administration of agmatine attenuates glutamate-induced neurotoxicity in cell cultures of rat cerebellum (Olmos et al, 1999), hippocampus (Wang et al, 2006), and cortex . Additionally, agmatine reduces infarct and loss of cerebellar neurons following in vivo focal or global ischemia (Gilad et al, 1996;Kim et al, 2004) and brain weight loss following ischemia in neonates (Feng et al, 2002). Behaviorally, agmatine dose-dependently attenuates behaviors associated with ethanol withdrawal, including stereotypy, tremor, and wet-dog shakes, without affecting motor coordination in nondependent animals (Uzbay et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous administration of agmatine attenuates glutamate-induced neurotoxicity in cell cultures of rat cerebellum (Olmos et al, 1999), hippocampus (Wang et al, 2006), and cortex . Additionally, agmatine reduces infarct and loss of cerebellar neurons following in vivo focal or global ischemia (Gilad et al, 1996;Kim et al, 2004) and brain weight loss following ischemia in neonates (Feng et al, 2002). Behaviorally, agmatine dose-dependently attenuates behaviors associated with ethanol withdrawal, including stereotypy, tremor, and wet-dog shakes, without affecting motor coordination in nondependent animals (Uzbay et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, agmatine inhibits the release of vasopressin in neurohypophysis [29] and norepinephrine from perivascular nerve terminals [9], suggesting a pre-synaptic action regulating the release of neuro-transmitters. Functional effects such as protection against ischemic neuronal injury [4,6,8,12,19,32,33] In initial experiments, we administered agmatine to rats (50 mg/kg, i.p.) and measured the levels of agmatine in cortex and hippocampus at different time points.…”
Section: Introductionmentioning
confidence: 99%
“…Agmatine has been shown to exert several actions that are related to its ability to inhibit NMDA receptors [4,19,30]. The protective effects of agmatine on excitotoxic injury in vitro and ischemic injury in vivo are well documented [4,6,11,12,32,33]. While the centrally administered agmatine potentiates morphine analgesia, peripheral agmatine reduces morphine tolerance and withdrawal symptoms [2,13,14,31].…”
mentioning
confidence: 99%
“…Agmatine also acts as an agonist at imidazoline receptors, inhibits nitric oxide synthase and interacts with alpha-2-adrenoceptors (Berkels et al 2004). Feng et al (2002) have suggested that agmatine reduces brain injury in neonatal rats exposed to hypoxia and ischemia as a result of its inhibitory effect on nitric oxide synthase. Because of its multiple interactions with receptors and enzymes agmatine represents a neurotransmitter that could increase in concentration during conditions such as cardiac arrest to prevent a variety of injurious brain activities.…”
Section: Discussionmentioning
confidence: 99%